Bakhtin's "Theory" of Genre - Clive Thomson (Studies in 20th & 21st Century Literature, 1984)
The originality of Bakhtin's fragmentary and partial theory of literary genre is underlined in this article. Bakhtin's reflexion on genre is very different from that of his Formalist contemporaries. Instead of proposing elaborate typologies or generic categories, Bakhtin more often devotes his attention to showing that a meaningful approach to the topic must be diachronic. From an epistemological point of view, the possibility of exact duplication or repetition of the same generic device from text to text is denied. Each text (or reading of a text) is a new performance in which generic material is reworked and re-presented. There are affinities, therefore, between the positions of Bakhtin and Fredric Jameson (in The Political Unconscious). Generic categories are useful only if they are seen as diagnostic tools which help us to better understand how texts enter into dialogic relations with each other.
Keywords: Bakhtin; literary genre; theory; typologies; generic; diachronic; epistemological; Fredric Jameson; The Political Unconscious; dialogic